Diagnosis and Treatment of Purulent Inflammatory Skin Diseases in Children - Karimova Zevara Hojibayevna; Nuritov Nurpullo Rajabovich (Zien Journals, 2022)
The paper summarizes the general principles and standardized diagnostic clinical symptoms of inflammatory skin diseases. A general concept ofpurulentsfcin diseases in children. Describes the clinical features, diagnosis and differential diagnosis of purulent skin diseases in children.Unsubstantiated diagnostic and therapeutic strategy.
Keywords: purulent diseases; sepsis